No Sib Pair Concordance for Breast or Ovarian Cancer in BRCA1 Mutation Carriers - Møller, Pål (BioMed Central, 2007)
Modifying factors might theoretically determine whether a BRCA1 mutation carrier contracts breast or ovarian cancer. If so, one would expect concordance for breast or ovarian cancer in affected sibships. We identified 64 pairs with cancers where one or both sisters were demonstrated to carry a BRCA1 mutation, and 116 additional constructed pairs in sibships with three or more affected sisters. We analysed concordance for breast and for ovarian cancer both in the complete series and in the 64 sister pairs alone. The results were that concordance for both breast and ovarian cancer in sisters was in keeping with random distribution or multiple and frequent modifying genetic factors. In conclusion, there may be no major modifying factor of expression of BRCA1 mutations. The practical implication of our findings is that previous disease manifestations in close relatives may have no bearing on the first cancer to be expected in a young female mutation carrier.